Implementasi Model Cooperative Learning Pada Managemen Pembelajaran Pendidikan Agama Islam Berbasis Multikultural Di SMK N 1 Kota Bengkulu - Rifky Septian, Rachmat; Harsena Dewa, Barata (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to investigate in depth the implementation of the Cooperative Learning model in the management of multicultural-based Islamic Religious Education (PAI) learning at SMK N 1 Bengkulu City, and to evaluate its effectiveness on the formation of morals and tolerance values. This study uses a qualitative approach with a descriptive-analytical case study method, which was chosen to examine the phenomenon in a specific vocational school environment. The study population includes all academic components involved in the PAI learning process, with a sample consisting of the Principal, PAI Teachers, and selected students, determined through a purposive sampling technique. Primary data collection was conducted through in-depth interviews, non-active participant observation in the classroom, and documentation studies such as Lesson Plans (RPP) and teacher notes. Data analysis used the qualitative analysis technique of the interactive model of Miles and Huberman, which includes data reduction, data presentation, as well as drawing conclusions and verification. The research findings reveal that the management of PAI learning successfully integrates multicultural values through a policy of forming very diverse groups, where Cooperative Learning acts as an effective social forum. Islamic Religious Education teachers act as managers of small-scale social conflicts, with an emphasis on managing social skills and group processing, which has a significant impact on increasing students' tolerance and empathy. This research recommendation highlights the importance of standardizing Islamic Religious Education classroom management curricula that explicitly adopt Cooperative Learning strategies as a managerial approach to addressing diversity in vocational schools.